Reproducibility and reliability of magnetic resonance imaging and B-mode ultrasound in ocular axial length measurement - Ghimire, Prasanna; Singh, Avinash; Sapkota, Hari (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Accurate ocular axial length (AL) measurement is critical for intraocular lens power calculation and refractive outcomes. While optical biometry is the clinical standard, dense media opacities limit its utility. This study evaluated B-mode ultrasound (B-USG) and MRI reproducibility and reliability for ocular AL measurement and assess inter-method agreement as alternative AL measurement methods.Methods: This prospective study included 102 adults (mean age 31.5±6.5 years) with normal ocular anatomy and emmetropic refraction. AL measurement used B-USG (9–12 MHz) and 1.5 Tesla MRI. Two blinded observers performed independent measurements; one repeated measurement after one day. Reliability was assessed using Intraclass Correlation Coefficient (ICC), Standard Error of Measurement (SEM), and Minimum Detectable Change (MDC). The agreement was evaluated using Bland–Altman analysis and Pearson correlation.Results: Mean AL was 23.618±0.726 mm for B-USG and 24.033±0.727 mm for MRI. Both methods showed excellent intraobserver (ICC=0.92 for ultrasound; ICC=0.95 for MRI) and inter-observer reliability (ICC=0.90 for ultrasound; ICC=0.93 for MRI). Strong linear correlation was observed (r=0.95, p